Le touriste et le terroriste ou les deux extrêmes du continuum transnational - Rosenau, James (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
This paper proceeds from the premise that profound changes have transformed the structure of world politics and that, consequently, a new, transnational paradigm of the global system needs to be developed. All the existing paradigms are found to be incapable of handling the proliferation of actors, the declining capacities of governments, the mushrooming of subgroup loyalties, the growing demands of the Third World, and the expansion of the range of issues on the global agenda - to mention only the most salient of the transformations that have rendered world politics both more decentralized and more complex. What is needed, it is argued, is a model organized around micro units of analysis that are common to both the new and old actors, issues, and structures and that thus form the foundation of the many new macro aggregations which have come to share the world stage with governments and international organizations.After developing a conception of four types of aggregational processes through which micro parts are converted into macro wholes, the analysis focuses on two types of transnational roles as worthy of consideration as the basic micro units of the new paradigm. The two types are designated as primitive and derivative roles. The former refers to roles in macro units that would not exist if their activities did not span national boundaries (the multinational corporation is an example), while the latter refers to roles in macro aggregations that do not depend on transnational interactions for their existence even though performances in them to have transnational consequences (examples are farmers, parents, and car drivers, who are both active and inadvertent participants in, respectively, today's global food, population, and energy issues).Whatever the issue involved, and irrespective of whether they are primitive or derivative, all transnational roles can be located on a legitimacy-authority continuum and seen as varying between two extremes, one which gives exclusive priority to the citizen role in a nation-state and the other which accords exclusive loyalty to the transnational role. The tourist and the terrorist are offered as examples of roles at the two extremes of this important continuum.